Eco-Friendly Business and Corporate Governance on Financial Performance Through Earnings Management - Christina Dwi Astuti; Etty Murwaningsari; Yvonne Augustine Sudibyo (Journal Research of Social Science, Economics, and Management, 2022)
This research aims to find the impact of Eco-friendly Business System Good and Corporate Governance Mechanisms on Financial Performance with Earning Management as a mediating variable. The samples are obtained from manufacturing companies listed on the Indonesian Stock Exchange from 2017-to 2019. The dependent variable in this research is Financial Performance, the independent variables are Eco-friendly Business systems and Good Corporate Governance, and the mediating variable is Earnings Management. Corporate Governance proxied by Independent Board of Commissioner, Institutional Ownership, and Audit Quality. This study is using a purposive sampling method. Data analysis using a regression model with SPSS tools. This research is expected to be able to provide information about factors that affect Financial Performance so it can be used as a consideration by investors and companies in making any decision. This research shows that an Eco-friendly Business System and Independent Board of Commissioner have a positive impact on Financial Performance, Audit quality hurts Earnings Management, and Earnings Management only mediates audit quality and financial performance. Institutional ownership has no direct and indirect effect on financial performance.